Functionalized liquid natural rubber and liquid epoxidized natural rubber: A promising green toughening agent for polyester. Issue 3 (8th August 2014) - Kargarzadeh, Hanieh; Ahmad, Ishak; Abdullah, Ibrahim; Thomas, Raju; Dufresne, Alain; Thomas, Sabu; Hassan, Aziz
ABSTRACT Toughened unsaturated polyester resins (UPRs) were prepared using two different reactive rubbers, namely, liquid natural rubber (LNR) and liquid epoxidized natural rubber (LENR). The effect of varying amounts of LNR and LENR on the morphology, thermal, and mechanical properties of UPR were evaluated. Fourier Transform Infrared spectroscopy was used to investigate the probable crosslinking reaction and changes in the functional groups on crosslinking. Field emission scanning electron microscopy and infinite focus microscopy were used to study the morphology of fracture surfaces. Tensile test showed that both the rubber‐modified resins (1.5 wt %) improved tensile strength. The viscoelastic properties and thermal stability of the toughened polyesters were evaluated using dynamic mechanical thermal analysis and thermogravimetric analysis, respectively. A slight reduction in the glass transition temperature (Tg) of the polyester was reported on the addition of both the rubbers. An increment in impact strength and fracture toughness was observed at 1.5 wt % for LNR and 4.5 wt % for LENR‐modified UPR. The results showed that both the liquid rubbers improved the mechanical properties of UPR. However, LENR‐modified UPR exhibited a more significant improvement in the mechanical properties compared to LNR‐modified UPR. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41292.